Little Angels - Peet, Mal; Illustred by Ian Newsham; Series Edited by Keith Gaines (Pakistan Oxford University Press, 1999)
In these stories, early school experiences are brought to life through a cast of lovable characters and children learn specific vocabulary in context. The "Oxford Literacy Web" is a literacy programme designed to guide schools through the primary years.
Included Color Illustrated
Keywords: Readers (Elementary)